COMPARING MYTH AND FOLKLORE IN WOLE SOYINKA AND GIRISH KARNAD - NISHA SHREE (International Journal of Multidisciplinary Research and Studies, 2021)
Myth and ritual have been practised in the vast majority of the world's cultures. The beginnings of mythology and the reasons why they were created are an inescapable aspect of the annals of human history. This comparative study of myth and rituals in select plays by Wole Soyinka and Girish Karnad will bring up the themes of sacrifice, rejuvenation, and fidelity through the lens of myth and rituals in those select plays. The title of this paper is "Comparative study of myth and rituals in the select plays of Wole Soyinka and Girish Karnad." The plays by Wole Soyinka and Girish Karnad that will be examined are "The Strong Breed" and "Naga-Mandala," respectively. The research would offer insight on the extent to which these two authors' mythological awareness becomes a powerful weapon to remark upon the modern world. The mythopoeic visions of these postcolonial writers represent the ethos of their different cultures via the development of theatrical forms, so recalling both the legendary powers and real performances of their original culture. In addition to this, the paper would shed light on the role that myths and rituals play in bringing both the individual and the entire society together. In the article, sociological theory would be utilised in an effort to demonstrate how myths and rituals have an effect, not only on the human mind, but also on the society to which that individual belongs.